Perilaku Konsumtif Pengguna PayLater dalam Perspektif Ekonomi Islam: Kajian terhadap Prinsip Maslahah, Wasathiyah, Israf, dan Tabdzir - Arya Nirwansyah Dwi Putra; Mukhtar Lutfi; Amiruddin Kadir (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2026)
The rapid growth of Buy Now Pay Later (BNPL) services, known as PayLater, in Indonesia has driven increased usage, especially among young people. However, this convenience also raises concerns about consumptive behavior that conflicts with the principles of Islamic economics. This study aims to analyze the consumptive behavior of PayLater users from the perspective of Islamic economics through the principles of maslahah (public interest), wasathiyah (moderation), israf (excessiveness), and tabdzir (wasteful spending). The research employs a qualitative approach using library research methods. Data were collected from books, academic journals, official reports, and relevant publications, then analyzed using content analysis techniques involving data reduction, classification, interpretation, and synthesis. The findings indicate that PayLater is essentially a neutral financial instrument that can provide maslahah when used to meet needs that offer real benefits and align with the user’s financial capacity. Nevertheless, the ease of access offered by PayLater may encourage consumptive behavior, impulsive purchases, and lifestyle-based consumption. This contradicts the principle of wasathiyah and may lead to israf and tabdzir. Therefore, from the perspective of Islamic economics, the use of PayLater requires self-control, Sharia financial literacy, and a consumption orientation based on maslahah to remain consistent with Islamic economic values.